An Australian rental housing conditions research infrastructure - Baker, E.; Daniel, L.; Beer, A.; Bentley, R.; Rowley, Steven; Baddeley, M.; London, K.; Stone, W.; Nygaard, C.; Hulse, K.; Lockwood, A. (NATURE PORTFOLIO, 2022)
Each year the proportion of Australians who rent their home increases and, for the first time in generations, there are now as many renters as outright homeowners. Researchers and policy makers, however, know very little about housing conditions within Australia’s rental housing sector due to a lack of systematic, reliable data. In 2020, a collaboration of Australian universities commissioned a survey of tenant households to build a data infrastructure on the household and demographic characteristics, housing quality and conditions in the Australian rental sector. This data infrastructure was designed to be national (representative across all Australian States and Territories), and balanced across key population characteristics. The resultant Australian Rental Housing Conditions Dataset (ARHCD) is a publicly available data infrastructure for researchers and policy makers, providing a basis for national and international research.